2012
DOI: 10.1007/s00213-012-2723-z
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in the treatment of challenging behaviour in adults with autism spectrum disorder

Abstract: This is the first case series of adults with ASD presenting with challenging behaviour who have been treated with aripiprazole. While the results are promising, controlled trials are required to confirm the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Multiple studies of aripiprazole for challenging behaviors in children and adolescents with ASD have reported efficacy, although SIB as a primary target symptom has not yet been specifically assessed Owen et al 2009;Stigler et al 2009). Small studies of aripiprazole in adults with ASD have found some improvements in maladaptive behavior, although there continues to be more evidence supporting its use in children (Jordan et al 2012). The potential side effects of increased appetite, weight gain and metabolic abnormalities can also be a concern or limiting factor in the use of aripiprazole (Wink et al 2010).…”
Section: Atypical Antipsychoticsmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple studies of aripiprazole for challenging behaviors in children and adolescents with ASD have reported efficacy, although SIB as a primary target symptom has not yet been specifically assessed Owen et al 2009;Stigler et al 2009). Small studies of aripiprazole in adults with ASD have found some improvements in maladaptive behavior, although there continues to be more evidence supporting its use in children (Jordan et al 2012). The potential side effects of increased appetite, weight gain and metabolic abnormalities can also be a concern or limiting factor in the use of aripiprazole (Wink et al 2010).…”
Section: Atypical Antipsychoticsmentioning
confidence: 97%
“…Aripiprazole is a unique atypical antipsychotic with partial agonism at the D 2 and 5HT 1A receptors, and antagonism at the 5HT 2 receptor (Jordan et al 2012). Like risperidone, it has been approved by the FDA for the treatment of irritability associated with ASD in children and adolescents (Wink et al 2010).…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%
“…Par exemple, on retrouve dans cette catégorie des études sur la prévalence des prescriptions d'antipsychotiques chez une population étudiée (Deb, Unwin et Deb, 2015;Griffiths, Halder et Chaudhry, 2012) ou l'efficacité d'une molécule (p. ex., « Aripiprazole », « Clozapine » ou « Levetiracetam ») pour la gestion des TGC (Deriaz, Willi, Orihuela-Flores, Galli Carminati et Ratib, 2012;Jordan, Robertson, Catani, Craig et Murphy, 2012;Kiani et al, 2015;Vowels, Lingappa et Bastiampillai, 2014). Une seule étude recensée utilise une méthode longitudinale pour mesurer les effets du sevrage de la médication antipsychotique sur des paramètres métaboliques, dont l'indice de masse corporel (de Kuijper, Mulder, Evenhuis, Visser et Hoekstra, 2013).…”
Section: Méthodeunclassified
“…Les auteurs cherchent principalement à mesurer les effets du traitement pharmacologique offert dans le milieu d'hébergement ou à connaître les raisons pour lesquelles les médicaments ont été prescrits. Le modèle médical utilise les termes « amélioration » (much improve), « très grande amélioration » (very much improve) ou « bénéfices » (benefits) pour indiquer les effets positifs du traitement sur la personne (Jordan et al, 2012;Kiani et al, 2015). Dans cette perspective, l'individu et ses caractéristiques sont traités comme des variables statiques influençant la résultante du traitement.…”
Section: Sujets D'étude Convergents Ou Divergents Selon Les Deux Modèunclassified
“…The effi cacy of aripiprazole has been established for the treatment of schizophrenia [ 2 ] . It is also reported that aripiprazole is effi cacious for a range of symptoms associated with pervasive developmental disorders [ 3 ] . Aripiprazole undergoes N-dealkylation, hydroxylation and dehydrogenation, yielding its active metabolite [ 4 ] , dehydroaripiprazole.…”
Section: Eff Ects Of Escitalopram On Plasma Concentrations Of Aripiprmentioning
confidence: 99%